MODIFICATION OF POCUNG SONG IN ETHNOMATHEMATICS-BASED LEARNING FOR THE TOPICS OF LENGTH MEASUREMENTS - Lilis Risma Putri; Hanifah Mar'atush Shalihah; Asma' Khoirunnisa'; Heru Sukoco (Universitas negeri Yogyakarta, 2023)
Learning in measuring units of length is basically inseparable from familiar objects in the society, one of which is traditional songs. This study was aimed at finding whether using the tune of a traditional song in Yogyakarta, namely Pocung song, and modifying the lyrics with mathematical contents can facilitate students to think mathematically. This study used the pre-experimental design method with the one-group pre-test-posttest design model. The research subjects were 10 3rd grade students of a cultural elementary school in Gunungkidul. The results showed that the modification of the Pocung song in ethnomathematics-based mathematics learning in the length-unit competencies was developed in an audio-visual form which could be accessed via the YouTube and the implementation ofthe Pocung song modification in ethnomatematics-based learning in the length-unit competencies had a positive influence on students’ learning achievements.